Forest Changes in the Great Lakes Region at 5-7 ka BP - Anderson, Thane (Géographie physique et Quaternaire, 1995)
ABSTRACTPollen stratigraphy from 90 sites in and bordering the Great Lakes record the 5-7 ka history of forest development of the Great Lakes region. By 7 ka beech (Fagus grandifolia) had invaded the oak-hickory (Quercus-Carya) forest of lower Michigan and hemlock (Tsuga canadensis) and beech the white pine (Pinus strobus)-dominated forest of southern Ontario. At the same time, white pine replaced jack pine (P banksiana) as it expanded northward to the Clay Belt beyond its present-day range. Forest changes at 6 and 5 ka were dominated by range extensions of beech and hemlock in a northwesterly direction, by northward expansion of eastern white cedar (Cupressineae), and southward migration of white pine into the Michigan basin. The beech and hemlock migrations (160 m yr-1 and 280 m yr-1, respectively) may have been influenced by the cool-moist climate generated by the Nipissing Great Lakes in combination with enhanced regional warming. White pine and eastern white cedar responded to regional warming and reduced precipitation, whereas birch (Betula) and alder (Alnus) may have been influenced more by fire activity caused by the warm-dry climate. The boreal-mixed forest ecotone was displaced 140 km northward at 5-7 ka compared to 60-70 km for the mixed-deciduous forest ecotone.